2022
DOI: 10.1038/s41525-022-00311-2
|View full text |Cite
|
Sign up to set email alerts
|

Allelic overload and its clinical modifier effect in Bardet-Biedl syndrome

Abstract: Bardet–Biedl syndrome (BBS) is an autosomal recessive ciliopathy characterized by extensive inter- and intra-familial variability, in which oligogenic interactions have been also reported. Our main goal is to elucidate the role of mutational load in the clinical variability of BBS. A cohort of 99 patients from 77 different families with biallelic pathogenic variants in a BBS-associated gene was retrospectively recruited. Human Phenotype Ontology terms were used in the annotation of clinical symptoms. The mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The presence/absence of modifier alleles helps in genetic counseling and has potential disease management benefits when identified earlier. 61 Further in silico or in vitro assays are required to identify and confirm the epistatic effect, if any, among the BBS genes observed in families II and IV. Figure 3 shows the cosegregation analysis performed these pedigrees.…”
Section: Intrafamilial Phenotypic Variabilitymentioning
confidence: 99%
“…The presence/absence of modifier alleles helps in genetic counseling and has potential disease management benefits when identified earlier. 61 Further in silico or in vitro assays are required to identify and confirm the epistatic effect, if any, among the BBS genes observed in families II and IV. Figure 3 shows the cosegregation analysis performed these pedigrees.…”
Section: Intrafamilial Phenotypic Variabilitymentioning
confidence: 99%
“…Instead, BBS12 p.Arg355* was overabundant in our cohort and contributed to BBS12 emerging as the most common causal gene. Still, BBS12 is among the major contributors to BBS accounting for 8%–11% in most reported cohorts (Khan et al, 2016; Stoetzel et al, 2007), including a recent study of 99 affected individuals for which BBS12 was causal in 14% of cases (Perea‐Romero et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although the rarity of BBS and underlying genetic heterogeneity limit conclusive statements about commonly observed gene pairings, some genes appear to be more frequently implicated in oligogenic phenomena. In a recent study, BBS1 , BBS4 , BBS2 , CFAP418/BBS21 , and BBS12 were reported as common driver genes involved in oligogenic phenomena (Perea‐Romero et al, 2022). Accordingly, we detected a third allele in two families with primary causal variants in BBS12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanistic downstream effect and functional consequences have never been assessed [15,16]. Examples of digenicity in hereditary kidney disease include Alport syndrome caused by pathogenic alterations in more than one of the three COL4A3-5 genes [17]; cystinuria with variants in both SLC3A1 and SLC7A9 [18]; and Bardet-Biedl syndrome, wherein oligogenicity has been postulated for a long time [19].…”
Section: Introductionmentioning
confidence: 99%